2009
DOI: 10.1080/02652030903161580
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion behaviour of tinplate cans in contact with tomato purée and protective (inhibiting) substances

Abstract: The dissolution of iron and tin from tinplate cans filled with tomato purée (pH 4.34) and dioctyl sebacate oil (DOS), essential onion oil (EOO) or potassium nitrate was studied using atomic absorption spectroscopy (AAS), while nitrate was determined using high-performance liquid chromatography (HPLC). The maximum values found in cans were up to 284 mg kg(-1) for tin and 513 mg kg(-1) for iron at elevated storage temperature. Results indicated that the addition of EOO to tomato purée prevents the corrosion proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 18 publications
1
15
0
Order By: Relevance
“…The results point out that in the canned samples with EOO at higher temperature (BN 0.1g36 and BSN 0.1g36) pitting type of corrosion occurred (anodic oxidation of Fe and development of H 2 ) as a result of EOO adsorption probably through sulfur atoms on the tinplate surface. The mass fractions of iron in these samples are extremely high; from 29.5 to 498.4 mg kg −1 for BN 0.1g36 and from 25.9 to 513 mg kg −1 for BSN 0.1g36 28. The values obtained exceed the maximally permitted limit3 of 50 mg kg −1 already after 30 days of storage and as such indicate a serious corrosion problem, which was not evident after the visual inspection of inner part of the empty cans, covered with a uniform violet film.…”
Section: Results and Discusionmentioning
confidence: 91%
See 2 more Smart Citations
“…The results point out that in the canned samples with EOO at higher temperature (BN 0.1g36 and BSN 0.1g36) pitting type of corrosion occurred (anodic oxidation of Fe and development of H 2 ) as a result of EOO adsorption probably through sulfur atoms on the tinplate surface. The mass fractions of iron in these samples are extremely high; from 29.5 to 498.4 mg kg −1 for BN 0.1g36 and from 25.9 to 513 mg kg −1 for BSN 0.1g36 28. The values obtained exceed the maximally permitted limit3 of 50 mg kg −1 already after 30 days of storage and as such indicate a serious corrosion problem, which was not evident after the visual inspection of inner part of the empty cans, covered with a uniform violet film.…”
Section: Results and Discusionmentioning
confidence: 91%
“…This study also confirmed that cans from two different groups (with and without nitrates) behave identically. Addition of nitrates had no influence on the production of H 2 , but it accelerates the dissolution of tin 28. During storage, the nitrates are reduced through a number of intermediates to ammonia and act as corrosion accelerators.…”
Section: Results and Discusionmentioning
confidence: 98%
See 1 more Smart Citation
“…In order to avoid the tin and iron contamination, lacquers or different kinds of corrosion inhibitors can be used in order to protect the surface of the container (Nincˇevicˇ Grassino et al. ). Although corrosion can form under the layer of lacquer due to a variety of reasons such as improper uniform coating, damaged layer during manufacturing, and packaging or the influence of other physical or chemical factors (Platonova ).…”
Section: Resultsmentioning
confidence: 99%
“…Containers for canning are usually made of tin (Sn)‐plated steel because Sn has low toxicity and high corrosion resistance. However, acidic foods like tomato paste can result in elevating the rate of dissolution of Sn . Human exposure to Sn occurs mainly through dietary intake of foods from tin‐plated cans .…”
Section: Introductionmentioning
confidence: 99%